Phytochemical content in Polyalthia bullata king and the effect of auxins, elicitors and precursors on total alkaloid content in callus - Kamarul Zaman, Munirah Adibah (2020)
Polyalthia bullata or locally known as Tongkat Ali Hitam is one of the species belongs to genus of Polyalthia. The plant has been reported to possess an ability to treat many diseases and enhance human health and life quality, which might be contributed by the presence of bioactive compounds. However, due to limited reports on phytochemical compounds present in P. bullata, the phytochemical profiling can help in clarifying the types of phytocompounds, therefore, choosing the right extraction solvent is important in order to get optimum yield. One of the factors that might affect the extraction yield is the polarity of extraction solvent. Apart from that, overcollection of P. bullata from wild habitat has become serious problem that may lead to species extinction. The establishment of P. bullata callus culture and addition of elicitors and precursors can help in enhancing the production of phytochemical compounds, therefore reducing the extinction of P. bullata from native habitat. Hence, the aims of this study were to determine the total alkaloid content (TAC), total phenolic content (TPC), total flavonoid content (TFC), and total terpenoid content (TTC) as well as antioxidant activity of hexanic, ethanolic, methanolic, and distilled water extracts of P. bullata root, leaf and stem, to profile biochemical compounds using gas chromatography- mass spectrometry (GC-MS), to induce callus from P. bullata using different explants, basal media, and plant growth regulators (PGRs), and to determine the effectiveness of auxins, precursors, and elicitors in enhancing alkaloid production in callus. For callus induction, the sterilized leaf and midrib explants were used and cultured on Murashige and Skoog (MS) and Woody Plant Medium (WPM) basal media supplemented with B5 vitamin, and different concentrations and types of auxins (2,4-dichlorophenoxyacetic acid (2,4-D), α- naphthaleneacetic acid (NAA), picloram and dicamba). The MS and WPM basal media supplemented with different types and concentrations (10, 20, 30, 40 50 μM) of auxins (2,4-D, NAA, picloram, dicamba, indole-3-acetic acid (IAA), indole-3-butyric acid (IBA)) were used to determine the best multiplication medium and alkaloid content after six weeks of culture. The elicitors (methyl jasmonate (MeJA), salicylic acid (SA), and chitosan) and precursors (L-phenylalanine, L-tyrosine, and L-tryptophan) at concentration of 50, 100 and 150 μM was respectively added into the best alkaloid production medium to enhance the alkaloid production. The results from the studies revealed that the methanolic extract of P. bullata leaf exhibited the highest TPC, TFC, TTC and total antioxidant activity at 1042.52 ± 1.97 mg GAE/g DW, 80.88 ± 0.24 mg QE/g DW, 0.19 ± 0.00 mg LE/g DW and 85.19 ± 1.16%, respectively. Meanwhile, the methanolic extract of P. bullata stem showed the highest TAC at 7.71 ± 0.00 mg AE/g DW. The fatty acids, phenolics, and carboxylic acid were found in methanolic stem extract; carbohydrates, alkaloids, and fatty acids were found in methanolic root extract; and terpenoids, phenolics, and alcohol were found in methanolic leaf extract of P. bullata using GC-MS. Among the media tested for in vitro callus induction, WPM basal medium supplemented with 16.56 μM picloram exhibited the highest callus induction percentage with 53.33 ± 22.06%. As for the callus multiplication, the callus cultured on MS + 30 μM dicamba was found to significantly produce the highest fresh weight (1180.00 ± 159.43 mg FW) and dry weight (58.00 ± 6.66 mg DW) of callus after three weeks of culture. The addition of auxins into culture medium managed to enhance the alkaloid production in callus with the highest alkaloid content was observed in callus cultured on MS medium supplemented with 30 μM 2,4-D (31.07 ± 0.05 μg/g DW). Among auxins, elicitors, and precursors tested, the MS + 30 μM 2,4-D and MS + 30 μM 2,4-D + 50 μM chitosan were found to be the best media for alkaloid production with the amount of 31.07 ± 0.05 and 31.30 ± 0.23 μg/mg DW after six weeks of culture, respectively. As a conclusion, methanol was found to be the best extraction solvent to extract phytochemical compounds from P. bullata. The incorporation of auxins like 2,4-D into the culture medium is the best strategy to enhance alkaloid production in P. bullata callus. Therefore, the data obtained from this study can be used to further investigate biological activities of phytochemical compounds present in P. bullata, and therefore can reduce overcollection of this plant from the forest.